2016
DOI: 10.1086/685585
|View full text |Cite
|
Sign up to set email alerts
|

Moderate as Necessary: The Role of Electoral Competitiveness and Party Size in Explaining Parties’ Policy Shifts

Abstract: This article investigates how the degree of electoral competition affects parties' policy positions. It follows a growing body of research on party positioning in multiparty competition that regards elections as signals for parties that have to choose their positions and issue strategies. In this article we argue that previous elections provide information about the competitiveness of the upcoming election. The expected degree of electoral competition affects parties' future policy positions since with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 50 publications
2
45
1
Order By: Relevance
“…Importantly, scholars have also found that parties benefit electorally when moderating their positions in multiparty systems (see, e.g., Ezrow ; Adams & Somer‐Topcu ; Abou‐Chadi & Orlowski ). When electoral competition is high, for example, Abou‐Chadi and Orlowski () find that large mainstream parties will moderate their positions.…”
Section: Mainstream Party Convergence and Vote Switchingmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, scholars have also found that parties benefit electorally when moderating their positions in multiparty systems (see, e.g., Ezrow ; Adams & Somer‐Topcu ; Abou‐Chadi & Orlowski ). When electoral competition is high, for example, Abou‐Chadi and Orlowski () find that large mainstream parties will moderate their positions.…”
Section: Mainstream Party Convergence and Vote Switchingmentioning
confidence: 99%
“…Importantly, scholars have also found that parties benefit electorally when moderating their positions in multiparty systems (see, e.g., Ezrow ; Adams & Somer‐Topcu ; Abou‐Chadi & Orlowski ). When electoral competition is high, for example, Abou‐Chadi and Orlowski () find that large mainstream parties will moderate their positions. Rovny (), moreover, has argued that parties may choose to blur issues they wish to de‐emphasise and Somer‐Topcu () has demonstrated that parties in multiparty systems that use a ‘broad appeal strategy’ do better electorally.…”
Section: Mainstream Party Convergence and Vote Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…And indeed, some studies can demonstrate how varying degrees of competition affect policy making and social policy more specifically (Hobolt & Klemmensen 2008;Immergut & Abou-Chadi 2014;Hübscher & Sattler 2017). This is achieved in two steps: the derivation of an optimisation problem from a set of inequalities describing the bargaining position of each party in a legislature; and the estimation of seatsvotes curves for all parties to express every party's seat share as a function of its own and every other party's vote share (Abou-Chadi & Orlowski 2016). We thus rely on the measure provided by Abou-Chadi and Orlowski (2016), which is the only measure that truly varies at the party level.…”
Section: Data Operationalisation and Methodsmentioning
confidence: 99%
“…We define the degree of electoral competition as the probability that a vote shift will occur that changes a party's bargaining position in parliament (Abou-Chadi & Orlowski 2016). First, we examine the link between these electoral incentives and policy outcomes; and second, we place the intensity and directionality of electoral competition at the centre of the analysis.…”
Section: Introductionmentioning
confidence: 99%